Rogue Protocol - Wells, Martha (Wells, Martha. Murderbot diaries., 2018)
"Sci-Fi's favorite antisocial AI is back on a mission. The case against the too-big-to-fail GrayChris Corporation is floundering, and more importantly, authorities are beginning to ask more questions about where Dr. Mensah's SecUnit is. And Murderbot would rather those questions went away. For good."